Role of trans vaginal sonography with hysteroscopy in detection of uterine causes of abortions - Vishwakarma, Shubhi; Khari, Sonia; Verma, Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Recurrent pregnancy loss (RPL) is one of the most frustrating and difficult areas in reproductive medicine because the aetiology is often unknown and there are only few evidence-based diagnostic and treatment strategies. Objective of this study was to compare the role of trans vaginal sonography with hysteroscopy in detection of uterine causes of abortions. Methods: This prospective cohort study was conducted in the department of obstetrics and gynaecology, Kasturba Hospital, Daryaganj, Delhi. The study was conducted from January 2016 to December 2016. Results: On transvaginal sonography majority of women i.e. 39(78%) patients had normal ultra-sonographic findings. 11(22%) showed various abnormal findings. Most commonly diagnosed abnormal finding on TVS was polyp, seen in 5(10%) patients. It was seen as a well-defined, uniformly hyperechoic mass within the endometrial cavity. normal hysteroscopic findings were seen in 27(54%) patients. Rest 23(46%) patients had abnormal uterine factors as diagnosed by hysteroscopy.Synechiae was detected in 9(18%) patients. It was the most common abnormality detected on hysteroscopy. Out of 9 patients who had synechiae, 2 had severe dense adhesions. In 6 patients, the adhesions were mild and flimsy. While minimal adhesions were noted in 1 patient, seen near the cornua. Conclusions: hysteroscopy is still the gold standard for diagnosis and most definitive procedure of choice if any kind of operative intervention is required.